Examining factors influencing sentencing decisions in school shootings. Issue 1 (9th January 2017) - McKenzie, Sherzine; William Crosby, James
Abstract : Purpose: The purpose of this paper is to examine public perception of factors relevant in sentencing decision making for juvenile school shooters with a history of familial abuse, peer victimization, and school intervention. Design/methodology/approach: Through the use of school shooting vignettes, 298 college-aged participants were randomly assigned to one of eight experimental conditions which differed based on the inclusion of the independent variables. Findings: Results revealed no significant differences among the groups on the sentencing recommendations (i.e. psychiatric placement and incarceration). However, correlational analyses indicated that participants' generally perceived they were influenced by the perpetrator's history of peer victimization and the level of intervention offered by school personnel when the shooter was bullied. Further regression analyses suggested that participant characteristics such as race, gender, and prior experiences with bullying were among the most powerful predictors of agreement with sentencing recommendations. Practical implications: Implications of the current findings raise questions as to the influence of peer victimization in civil and criminal court proceedings and its associated impact on the juvenile justice system, the educational system, and society's desire for justice. Originality/value: This study ambitiously ventures into exploring and understanding the relevant sociological, academic, and legal factors in addressing acts of school violence.